Determination of K4000 of potential blazar candidates among EGRET unidentified gamma-ray sources. Issue Volume 15:Issue S356(2019) (October 2019) - Uwitonze, Emmanuel; Nkundabakura, Pheneas; Mutabazi, Tom
Abstract: Blazars are radio-loud Active Galactic Nuclei (AGN) with relativistic jets oriented towards the observer's line-of-sight. Based on their optical spectra, blazars may be classified as flat-spectrum radio quasars (FSRQs) or BL Lacs. FSRQs are more luminous blazars with both narrow and broad emission and absorption lines, while BL Lacs are less luminous and featureless. Recent studies show that blazars dominate (˜93%) the already-identified EGRET sources (142), suggesting that among the unidentified sources (129) there could still be faint blazars. Due to the presence of a strong non-thermal component inside their jets, blazars are found to display a weaker depression at ˜4000 Å (K 4000 ≤ 0.4). In this study, we aimed at determining the K 4000 break for a selected sample among the potential blazar candidates from unidentified EGRET sources to confirm their blazar nature. We used two blazar candidates, 3EG J1800-0146 and 3EG J1709-0817 associated with radio counterparts, J1802-0207 and J1713-0817, respectively. Their optical counterparts were obtained through spectroscopic observations using Robert Stobie spectrograph (RSS) at the Southern African Large Telescope (SALT) in South Africa. The observed Ca II H & K lines depression at ˜4000 Å in spectra of these sources show a shallow depression, K 4000 = 0.35 ± 0.02 and 0.24 ± 0.01, respectively, suggesting that these sources are blazar candidates. Moreover, the redshifts z = 0.165 and 0.26 measured in their spectra confirm the extragalactic nature of these sources.